A Highly Stable Zeotype Mesoporous Zirconium Metal–Organic Framework with Ultralarge Pores. (10th November 2014) - Feng, Dawei; Wang, Kecheng; Su, Jie; Liu, Tian‐Fu; Park, Jihye; Wei, Zhangwen; Bosch, Mathieu; Yakovenko, Andrey; Zou, Xiaodong; Zhou, Hong‐Cai
Abstract: Through topological rationalization, a zeotype mesoporous Zr‐containing metal–organic framework (MOF), namely PCN‐777, has been designed and synthesized. PCN‐777 exhibits the largest cage size of 3.8 nm and the highest pore volume of 2.8 cm 3  g −1 among reported Zr‐MOFs. Moreover, PCN‐777 shows excellent stability in aqueous environments, which makes it an ideal candidate as a support to incorporate different functional moieties. Through facile internal surface modification, the interaction between PCN‐777 and different guests can be varied to realize efficient immobilization. Abstract : Topologische Planung ergibt ein zeotypes mesoporöses Zirconium‐organisches Gerüst. Durch Verknüpfung von Tetraedern (orange) aus [M3 O(COO)6 ]‐Knoten und dreizähnig bindenden Benzol‐1, 3, 5‐tricarboxylat‐Flächen in ekliptischer Konfiguration ( D 3 h ‐Knoten; hellblauer Stab) entsteht ein mtn‐Gerüst. Eine 60°‐Drehung der Tetraeder gegeneinander führt zur gestaffelten Konfiguration mit D 3 d ‐Knoten (dunkelblauer Stab) und zu einem β‐Cristobalit‐Gerüst.